2023
DOI: 10.1111/luts.12475
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vibegron compared with mirabegron for overactive bladder: A systematic review and network meta‐analysis

Abstract: Objectives: The aim of this study was to indirectly compare the efficacy and safety of mirabegron and vibegron in patients with overactive bladder.Methods: A systematic search was performed on Pubmed, Web of Science, Embase, and the Cochrane Central Register of Controlled Trials databases to identify studies from the date of database inception to January 1, 2022. All randomized controlled trials comparing mirabegron or vibegron with tolterodine, imidafenacin, or placebo were eligible. One reviewer extracted da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Improvement in daily micturition was similar, but vibegron was associated with significant improvement in total incontinence episodes at week 4 and week 52 as well as voided volume at week 12 and week 52 [21,22]. The most recent systematic review and network meta-analysis concluded that both mirabegron and vibegron were comparable and welltolerated in OAB patients but vibegron might be more effective than mirabegron in improving mean voided volume per micturition [23]. Moreover, despite lack of available real-word data on persistence, vibegron was assumed to be cost-effective from a commercial payor and Medicare perspective when compared with other oral pharmacologic agents for OAB [24].…”
Section: Discussionmentioning
confidence: 96%
“…Improvement in daily micturition was similar, but vibegron was associated with significant improvement in total incontinence episodes at week 4 and week 52 as well as voided volume at week 12 and week 52 [21,22]. The most recent systematic review and network meta-analysis concluded that both mirabegron and vibegron were comparable and welltolerated in OAB patients but vibegron might be more effective than mirabegron in improving mean voided volume per micturition [23]. Moreover, despite lack of available real-word data on persistence, vibegron was assumed to be cost-effective from a commercial payor and Medicare perspective when compared with other oral pharmacologic agents for OAB [24].…”
Section: Discussionmentioning
confidence: 96%